KOMPARASI SISTEM PENDIDIKAN MESIR, AMERIKA, DAN JEPANG SEBAGAI PENUNJANG PERBAIKAN PENDIDIKAN DI INDONESIA DALAM TINJAUAN MUTU LULUSAN - Lia Emalia (LPPM Bunga Bangsa Cirebon, 2023)
Education as a system means a series of long processes of knowledge transfer. Therefore it can be said as a complex process, both from teachers, students, curriculum to supporting facilities. In improving the quality of graduates, the education system in Indonesia needs improvement in each of its elements. To examine the education system, the drafting team used a literacy study approach in comparing education systems in several developed countries, namely Egypt, the United States and Japan. The results of the literature review concluded that the Egyptian education system excels in religious education, the United States excels in realizing educational goals for a multi-cultural country and Japan in implementing character from an early age.